Answer:
7
Step-by-step explanation:
x2 + 5x - 7
sub x = 2 in
(2 X 2) + (5 X 2) - 7
4 + 10 - 7
= 7
Step-by-step explanation:
( secA + 1)( sec A - 1)
Using the expansion
( a + b)( a - b) = a² - b²
Expand the expression
We have
sec²A + secA - secA - 1
That's
sec² A - 1
From trigonometric identities
<h3>sec²A - 1 = tan ²A</h3>
So we have the final answer as
<h3>tan²A</h3>
As proven
Hope this helps you
Have you learned about the Pythagorean theorem? a² + b² = c² . . . you should teach them about this.
Answer:
m+5n+7
Step-by-step explanation:
5m-n+7-4m+6n
=5m-4m-n+6n+7
=m+5n+7